Xiong Shili's Explaining Mind : An Annotated Translation - Makeham, John, (Asian Studies E-Books Online, Collection 2026., 2026)
Explaining Mind is a representative text of Xiong Shili's mature onto-cosmology, moral psychology, and epistemology, in which he develops an extended account of mind, as both a moral concept and a metaphysical concept, while critically engaging key aspects of Buddhist, Daoist and Confucian thought. The book covers a diverse range of topics and themes, including the non-duality of Reality and function, philosophical psychology, the inherent mind and the habituated mind, the mind of humaneness, the inseparability of mind and matter, learning concerned with increasing knowledge daily (modern science) and learning concerned with removing ignorance daily (ancient philosophy), cultivation practices of Confucians and Buddhists, wisdom and knowledge, and the origin of badness and wrongdoing.